Towards Long-term Non-invasive Monitoring for Epilepsy via Wearable EEG Devices - Ingolfsson, Thorir Mar; Cossettini, Andrea; Wang, Xiaying; Tabanelli, Enrico; Tagliavini, Giuseppe; Ryvlin, Philippe; Benini, Luca; Benatti, Simone (2021 IEEE Biomedical Circuits and Systems Conference (BioCAS), 2021)
We present the implementation of seizure detection algorithms based on a minimal number of EEG channels on a parallel ultra-low-power embedded platform. The analyses are based on the CHB-MIT dataset, and include explorations of different classification approaches (Support Vector Machines, Random Forest, Extra Trees, AdaBoost) and different pre/post-processing techniques to maximize sensitivity while guaranteeing no false alarms. We analyze global and subject-specific approaches, considering all 23-electrodes or only 4 temporal channels. For 8 s window size and subject-specific approach, we report zero false positives and 100% sensitivity. These algorithms are parallelized and optimized for a parallel ultra-low power (PULP) platform, enabling 300h of continuous monitoring on a 300 mAh battery, in a wearable form factor and power budget. These results pave the way for the implementation of affordable, wearable, long-term epilepsy monitoring solutions with low false-positive rates and high sensitivity, meeting both patient and caregiver requirements.